Foreign Employment and Use of Remittance in Mahalaxmi Municipality of Lalitpur District in Nepal - Dahal, Ananta Raj (Cognition, 2019)
Foreign employment plays vital role in maintaining the Nepalese’s economy.Main source of information of this study is primary data and some secondary data are also used for the supplementary usage of the study. Primary data were collected through the direct questionnaire method used the semi-structured for the sample area of people who were selected by judgemental sampling method. Descriptive statistics has been used as the tools of data to analyse for the foreign employment and use of remittance in Nepal with reference to Mahalaxmi Municipality of Lalitpur district. Most of the youth belonging to 26-35 years old were involved in the foreign employment in the sample area. Maximum migrant people are involved in construction and industrial labour. They stay in foreign country (2-3) year at one time.Major destination for foreign employment is Malaysia and Qatar. The foreign employee people earn minimum Rs(20-30)thousand and maximum above Rs 60 thousand per month. They spend their maximum remittance income for food and education. By the help of remittance income earn through the foreign employment urban people also used physical facilities like rural people for their daily life.